Floristic and Phytoclimatic Study of a Sacred Grove Vegetation of West Midnapore District, West Bengal, India - Sen, Uday Kumar; Bhakat, Ram Kumar (Journal of Tropical Life Science, 2019)
Traditional cultural and religious beliefs and practices play a crucial role in the conservation of the environment and biodiversity in the form of the sacred groves. The present study was carried out to explore the plant resources, their biological spectrum, leaf size spectra, the conservation status of a sacred grove, locally known as Narampur Barapir Astana (NBA) in West Midnapore district of West Bengal in India. Floristic list of the study revealed that the vegetation of NBA was diverse and composed of 277 species belonging to 238 genera distributed over 77 families under 36 orders according to APG IV classification. The dominant order and family in terms of species richness were Lamiales 27 (9.75%) and Fabaceae 32 (11.55%) respectively. The biological spectrum shows the study area was classified as â€œthero-chamae-cryptophyticâ€ type of phytoclimate. As regards the leaf size spectra, mesophyll 56 (20.22%) was found to be high. The study area being a sacred grove is fairly undisturbed. For the long-term conservation of germplasm of the grove some recommendations are suggested.